PEMEROLEHAN FONEM ANAK USIA 2 SAMPAI 6 TAHUN - Nia Deby Septiyowati; Harun Ahmad Sangaji; Endang Sumarti (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2019)
This study aims to describe the acquisition of phonemes and stages of acquiring the form of a word sound for children aged 2;6 years. The research method that used is naturalistic observations carried out within a certain period of time (cross sectional). The subject of this study was a boy aged 2;6 years old named Muhammad Rizqy Al Amin. The results show that children aged 2;6 years have mastered the segmental phoneme, namely the vocal phonemes that have been mastered are [i], [], i], i], [e], [], e], ɛ], [a], a], a], [ǝ], ǝ], [o], [O], o], O], [u], [U], u], U] and the consonant phonemes that have been mastered are plosive [p, p’, b, t, t’, d], affricative [c, j, k, ?, g], fricative [s, h], lateral [l], tril [r], nasal [m, n, ñ, η], and semivocal [w, y]. Whereas the vowel phonemes that are still not mastered are [], a], [] and the consonants that are still not mastered are plosive [f, ], affricative [j’, k’, x, ɣ], fricative [f, , z, x], and lateral [L]. In addition to the segmental phoneme, children aged 2;6 years have also mastered suprasegmental phonemes, namely stress, tone/pitch, length, and juncture.Children aged 2;6 also experience sound changes in 36 words, as much as 2 to 5 times during the acquisition of observed language.